Mixed Method: Students’ Ability in Applying Writing Mechanics in Analytical Exposition Text - M. Fadhly Farhy Abbas; Nabila Firda Asy’ari (ELT-Lectura, 2019)
Based on the English syllabus of SMA Serirama YLPI Pekanbaru, the students should be able to write in English by paying attention to the linguistics elements. One of them is the use of writing mechanics. This study aimed at investigating students’ ability in applying writing mechanics in Analytical Exposition texts and explained the factors that influence students’ ability in applying writing mechanics in the eleventh grade of SMA Serirama YLPI Pekanbaru. The design of this research was mixed method. The population of this research was all the eleventh grade students of SMA Serirama YLPI Pekanbaru with total of 41 students. Sampling technique used in this research was total sampling. The instruments used were test and interview. Based on the result of the test, the average score of students’ ability in applying writing mechanics in an Analytical Exposition text was 71,56. Moreover, based on the interview result, the factors that influence the students’ ability in applying writing mechanics were the students lack of motivation to open dictionary to find the correct spelling of words, the difference between the pronunciation and written of words make students confused, and lack of student knowledge about writing mechanics. In conclusion, the students’ ability in applying writing mechanics in an Analytical Exposition text at the eleventh grade of SMA Serirama YLPI Pekanbaru is categorized into fair level caused by several factors.